Influence of induced disease states on the disposition kinetics of imidocarb in goats - Abdullah, Abdul Salam; Baggot, J. D. (Wiley, 1986)
The influence of fever, induced by different agents, on the disposition kinetics of imidocarb was determined in goats. Escherichia coli endotoxin (0.2 microgram/kg), Trypanosoma evansi (10(7) in 1 ml sterile glucose citrate), and Infectious Bovine Rhinotracheitis virus (10(6.5)TCID50) were the agents administered to induce the febrile state. In control and febrile animals the two-compartment model was used to describe the disposition kinetics of the drug. Fever caused significant changes to occur in the apparent volume of distribution and the body (systemic) clearance of imidocarb, but the half-life remained unchanged. The statistical significance of the changes in these pharmacokinetic parameters varied with the etiology of the febrile state. E. coli endotoxin and IBR virus caused corresponding decreases in apparent volume of distribution and clearance of imidocarb, while fever induced with T. evansi caused highly significant increases in both pharmacokinetic parameters. It was concluded that the alterations in the disposition kinetics of imidocarb that occurred in the febrile goats were related not only to the febrile reaction per se but also to the pathophysiology of the disease